Hamstring fatigue and muscle activation changes during six sets of Nordic hamstring exercise in amateur soccer players - Marshall, P. W. M.; Lovell, R.; Knox, M. F.; Brennan, S. L.; Siegler, J. C. (The Journal of Strength and Conditioning Research, 2015)
The Nordic hamstring exercise (NHE) is a bodyweight movement commonly prescribed to increase eccentric hamstring strength and reduce the incidence of strain injury in sport. This study examined hamstring fatigue and muscle activation responses throughout 6 sets of 5 repetitions of the NHE. Ten amateur-level soccer players performed a single session of 6 sets of 5 repetitions of NHE. Maximal eccentric and concentric torque output (in newton meters) was measured after every set. Hamstrings electromyograms (EMG) were measured during all maximal contractions and exercise repetitions. Hamstring maximal eccentric torque was reduced throughout the range of motion after only a single set of NHE between 7.9 and 17.1% (p = 0.05), with further reductions in subsequent sets. Similarly, maximal concentric torque reductions between 7.8 and 17.2% were observed throughout the range of motion after 1 set of NHE (p = 0.05). During the descent phase of the NHE repetitions, hamstring muscle activity progressively increased as the number of sets performed increased. These increases were observed in the first half of the range of motion. During the ascent phase, biceps femoris muscle activity but not medial hamstrings was reduced from the start of exercise during latter sets of repetitions. These data provide unique insight into the extent of fatigue induced from a bodyweight only exercise after a single set of 5 repetitions. Strength and conditioning coaches need to be aware of the speed and extent of fatigue induced from NHE, particularly in practical settings in which this exercise is now prescribed before sport-specific training sessions (i.e., the FIFA-11 before soccer training).